A review on carbohydrate embedded polyurethanes: An emerging area in the scope of biomedical applications. (1st February 2018) - Solanki, Archana; Das, Manita; Thakore, Sonal
Highlights: First review summarizing scope of diverse carbohydrates embedded polyurethanes. Processing techniques, biomedical applications and role of carbohydrates elaborated. Optimization of PU properties by the virtue of carbohydrate is highlighted. Economic and environmental benefits owing to use of natural raw materials discussed. Abstract: Polyurethanes (PUs) are expanding to newer horizons in the field of biomedical sciences, particularly due to their exceptional set of properties that deem fit for applications in the said field. On the other hand, carbohydrates find increasing attention as components of biomedical devices due to their easy availability from renewable resources. The manipulation of PUs by carbohydrate has solved the major concern of biodegradability, biocompatibility and economy. This review summarizes the recent trends in PUs embedded with carbohydrates ranging from monosaccharide to polysaccharides, including supramolecular host such as cyclodextrin etc. Diverse approaches for embedding them in PUs in various forms have been listed. In recent decade, significant research has been carried out to employ such polymers in biomedical applications such as drug delivery devices, implants, scaffolds for tissue engineering etc. This knowledge could facilitate the selection of more efficient approach for synthesis of polymeric systems based on the biological macromolecules.